Friends, Acquaintances, Pupils and Patrons Japanese Intellectual Life in the Late Eighteenth Century: A Prosopographical Approach - Beerens, Anna (LUP Dissertaties, 2006)
This study of the social circumstances of Japanese intellectuals in the last quarter of the eighteenth century is based on biographical data concerning 173 individuals. It deals with the image of intellectual life of that period in current scholarship, and with the self-image and ethos of scholars, authors, poets and artists. That self-image and ethos, however, often clash with the realities of their everyday lives. This prosopographical investigation offers a new look at intellectual life on a basic level. The current image of intellectual life in the Tokugawa period is one of dissatisfaction and withdrawal, whereas the image that results from this study is one of dynamism and interaction. For more (Dutch-language) titles on Japan, please visit: "http://www.aup.nl/do.php?a=show_visitor_booklist&b=series&series=21">www.aup.nl/japan